Lina and Serge the love and wars of Lina Prokofiev - Morrison, Simon Alexander 1964- (Houghton Mifflin Harcourt, 2013)
Chronicles the life of Lina Prokofiev, who followed her composer husband to Stalinist Russia, only to be left for another woman and incarcerated for eight years
Includes bibliographical references and index
Keywords: Prokofiev, Lina / 1897-1989; Prokofiev, Sergey / 1891-1953; Prokofʹev, Sergej Sergeevič -- 1891-1953; Prokofʹev, Lina -- 1897-1989; Sopranos (Singers) / Biography; Composers' spouses / Biography; Biografie